NATIONAL TRADITIONS ARE THE CRITERIA THAT FORM NATIONAL VALUES (Scientific journal of the Fergana State University, 2023)
The article analyzes the different aspects of the concepts of national customs, traditions and ceremonies, and the processes related to them linguistically. National characteristics of national traditions as national and universal values are analyzed based on examples. The factors affecting the creation and development of values and traditions are highlighted as an important factor that enriches the people's spirituality. Each ritual, which has become an ancient tradition of one or another people, is analyzed as a universal value, as a means of revealing the unique nature of human qualities, qualities of a perfect person